2021
DOI: 10.3389/fonc.2021.745719
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of m6A-Related lncRNA Signature as Potential Predictive Biomarkers in Breast Cancer

Abstract: The metastasis and poor prognosis are still regarded as the main challenge in the clinical treatment of breast cancer (BC). Both N6-methyladenosine (m6A) modification and lncRNAs play vital roles in the carcinogenesis and evolvement of BC. Considering the unknown association of m6A and lncRNAs in BC, this study therefore aims to discern m6A-related lncRNAs and explore their prognostic value in BC patients. Firstly, a total of 6 m6A-related lncRNAs were screened from TCGA database and accordingly constructed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…AL035587.1 is potentially modulated by m6A, m5C, and m1A RNA modifications in head and neck squamous cell carcinoma [ 39 ]. AL122010.1 is an immune- [ 40 ], stemness- [ 41 ], autophagy- [ 42 ], and m6A-relevant lncRNA [ 43 ] that enables to predict survival outcomes breast cancer. AC099850.3 is upregulated in LUAD and correlated to advanced stage, undesirable prognostic outcomes together with immune infiltration [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…AL035587.1 is potentially modulated by m6A, m5C, and m1A RNA modifications in head and neck squamous cell carcinoma [ 39 ]. AL122010.1 is an immune- [ 40 ], stemness- [ 41 ], autophagy- [ 42 ], and m6A-relevant lncRNA [ 43 ] that enables to predict survival outcomes breast cancer. AC099850.3 is upregulated in LUAD and correlated to advanced stage, undesirable prognostic outcomes together with immune infiltration [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the established models based on both m6A and other factors are attracting more and more attention. For instance, we previously constructed a risk signature based on 6 screened m6A-related lncRNAs, including Z68871.1, AL122010.1, OTUD6B-AS1, AC090948.3, AL138724.1, EGOT ( Lv et al, 2021 ). This model could identify the prognosis and immune state in BC.…”
Section: Discussionmentioning
confidence: 99%
“…Ten m 6 A-modified lncRNAs-LINC00571, ANKRD10- IT1, LINC00593, miR-205HG, CIRBP- AS1, BLACAT1, SUCLG2- AS1, SAMD12- AS1, BVES-AS1, a18SrRNA nd HOXB-AS1 were used to construct a prognostic score model, and may be potential predictors of survival in patients with TNBC ( Wu et al, 2021 ). A prognostic risk model comprised of six m 6 A-regulated lncRNAs-Z68871.1, AL122010.1, AL138724.1,OTUD6B-AS1, AC090948.3 and eosinophil granule ontogeny transcript (EGOT) for high-risk patients with tumor-infiltrating immune cells, indicated that m 6 A-regulated lncRNAs may modulate the immune microenvironment in breast cancer ( Lv et al, 2021b ). High expression of the m 6 A regulator hnRNPC, and low expression of hsa-miR-944, are associated with advanced stage breast cancer and poor prognosis ( Lv et al, 2021a ).…”
Section: Association Of Ribonucleic Acid Modification and Breast Canc...mentioning
confidence: 99%
“…These studies indicated that METTL3, METTL14, WTAP, FTO, ALKBH5, and other N6-methyladenosine-related lncRNAs were associated with progression of breast cancer, and may be prognostic indicators. Changes in expression and activity of m 6 A modulators may promote breast cancer progression ( Chen and Du, 2019 ; Lv et al, 2021b ; Zhang et al, 2021 ) ( Table 1 ). Few studies have mentioned m 5 C modifications and breast cancer, and most have focused on NSUN2.…”
Section: Association Of Ribonucleic Acid Modification and Breast Canc...mentioning
confidence: 99%